Styrene-maleic acid-copolymer conjugated zinc protoporphyrin as a candidate drug for tumor-targeted therapy and imaging. (27th May 2016) - Fang, Jun; Tsukigawa, Kenji; Liao, Long; Yin, Hongzhuan; Eguchi, Kanami; Maeda, Hiroshi
Abstract: Previous studies indicated the potential of zinc protoporphyrin (ZnPP) as an antitumor agent targeting to the tumor survival factor heme oxygenase-1, and/or for photodynamic therapy (PDT). In this study, to achieve tumor-targeted delivery, styrene-maleic acid-copolymer conjugated ZnPP (SMA-ZnPP) was synthesized via amide bond, which showed good water solubility, having ZnPP loading of 15%. More importantly, it forms micelles in aqueous solution with a mean particle size of 111.6 nm, whereas it has an apparent Mw of 65 kDa. This micelle formation was not detracted by serum albumin, suggesting it is stable in circulation. Further SMA-ZnPP conjugate will behave as an albumin complex in blood with much larger size (235 kDa) by virtue of the albumin binding property of SMA. Consequently, SMA-ZnPP conjugate exhibited prolonged circulating retention and preferential tumor accumulation by taking advantage of enhanced permeability and retention (EPR) effect. Clear tumor imaging was thus achieved by detecting the fluorescence of ZnPP. In addition, the cytotoxicity and PDT effect of SMA-ZnPP conjugate was confirmed in human cervical cancer HeLa cells. Light irradiation remarkably increased the cytotoxicity (IC50, from 33 to 5 μM). These findings may provide new options and knowledge for developing ZnPP based anticancer theranostic drugs.